A Core Outcome Set for Pediatric Critical Care*. Issue 12 (December 2020) - Fink, Ericka L; Maddux, Aline B.; Pinto, Neethi; Sorenson, Samuel; Notterman, Daniel; Dean, J. Michael; Carcillo, Joseph A.; Berg, Robert A.; Zuppa, Athena; Pollack, Murray M.; Meert, Kathleen L.; Hall, Mark W.; et al.
Abstract : Objectives: More children are surviving critical illness but are at risk of residual or new health conditions. An evidence-informed and stakeholder-recommended core outcome set is lacking for pediatric critical care outcomes. Our objective was to create a multinational, multistakeholder-recommended pediatric critical care core outcome set for inclusion in clinical and research programs. Design: A two-round modified Delphi electronic survey was conducted with 333 invited research, clinical, and family/advocate stakeholders. Stakeholders completing the first round were invited to participate in the second. Outcomes scoring greater than 69% "critical" and less than 15% "not important" advanced to round 2 with write-in outcomes considered. The Steering Committee held a virtual consensus conference to determine the final components. Setting: Multinational survey. Patients: Stakeholder participants from six continents representing clinicians, researchers, and family/advocates. Measurements and Main Results: Overall response rates were 75% and 82% for each round. Participants voted on seven Global Domains and 45 Specific Outcomes in round 1, and six Global Domains and 30 Specific Outcomes in round 2. Using overall (three stakeholder groups combined) results, consensus was defined as outcomes scoring greater than 90% "critical" and less than 15% "not important" and were included in the final PICU core outcome set: four Global Domains (Cognitive, Emotional, Physical, and Overall Health) and four Specific Outcomes (Child Health-Related Quality of Life, Pain, Survival, and Communication). Families ( n = 21) suggested additional critically important outcomes that did not meet consensus, which were included in the PICU core outcome set—extended. Conclusions: The PICU core outcome set and PICU core outcome set—extended are multistakeholder-recommended resources for clinical and research programs that seek to improve outcomes for children with critical illness and their families. Abstract : Supplemental Digital Content is available in the text.